Effect of light intensity and rhizobial inoculum on the performance of two tropical legumes - OGBOGHODO, I A (The Indian Journal of Agricultural Sciences, 2014)
A 22-week experiment was conducted in controlled environments to investigate the effects of light and inoculum application on the growth, nodulation and nitrogen fixation of 2 tropical legumes, viz Siris tree [Albizia lebbeck (L. Benth] and Subabul (Leucaena leucoceplala (Lam.) de Wit.]. Two light regimes-high light and low light (stimulated shade) were used. Plants were either inoculated without the addition of inorganic nitrogen or they received inorganic nitrogen without inoculum application. Control plants neither received inoculum nor inorganic nitrogen. The results showed that in both species under high light, the inoculated plants outgrew the uninoculated ones. Although there appears to have been more investment of the biomass. in the leaf area under simulated shade conditions for the inoculated plants. the lower net assimilation .rate resulled in lower growth rate. The controlled plants had the least growth under both light regimes, though they grew better under low light indicating that these legumes may be able to withstand nitrogen stress under shade conditions. Also more nodules were produced and more nitrogen fixed under high light than under the low light. Although nitrogen fixation was reduced under low light, nitrogen uptake was higher for Albizia lebbeck for the inoculated treatments than the uninoculated treatmentS.